2014
DOI: 10.1016/j.acvd.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width predicts mortality in infective endocarditis

Abstract: According to our results, mortality is high in patients with IE. RDW is a promising biomarker for predicting 1-year survival rates in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…The adjusted OR rose from1.12 to 1.40. RDW was reported as a binary variable in 2 studies [28, 33], and we found that the increased RDW levels were associated with a higher risk of death (OR, 2.12; 95%CI, 1.82–2.46) with low heterogeneity ( I 2 = 0, P = 0.49). And 4 studies provided data on AUC from 0.63 to 0.76 of RDW in prediction mortality [23, 25, 31, 33].…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…The adjusted OR rose from1.12 to 1.40. RDW was reported as a binary variable in 2 studies [28, 33], and we found that the increased RDW levels were associated with a higher risk of death (OR, 2.12; 95%CI, 1.82–2.46) with low heterogeneity ( I 2 = 0, P = 0.49). And 4 studies provided data on AUC from 0.63 to 0.76 of RDW in prediction mortality [23, 25, 31, 33].…”
Section: Resultsmentioning
confidence: 84%
“…RDW was reported as a binary variable in 2 studies [28, 33], and we found that the increased RDW levels were associated with a higher risk of death (OR, 2.12; 95%CI, 1.82–2.46) with low heterogeneity ( I 2 = 0, P = 0.49). And 4 studies provided data on AUC from 0.63 to 0.76 of RDW in prediction mortality [23, 25, 31, 33]. Finally, three studies reported RDW as a categorical variable [25, 27, 29], and a rank correlation was found between the RDW levels and mortality in these patients.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations